2019
DOI: 10.1111/jce.14264
|View full text |Cite
|
Sign up to set email alerts
|

The effect of posture, exercise, and atrial pacing on atrioventricular conduction in systolic heart failure

Abstract: Background Optimization of atrioventricular (AV) intervals for cardiac resynchronization therapy (CRT) programming is typically performed in supine patients at rest, which may not reflect AV timing in other conditions. Objective To evaluate the effects of posture, exercise, and atrial pacing on intrinsic AV intervals in patients with CRT devices. Methods Rate‐dependent A‐V delay by exercise was a multicenter, prospective trial of patients in sinus rhythm following CRT implantation. Intracardiac electrograms we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…As shown previously, ARV and ALV intervals increased rapidly in all subjects from atrial sense to atrial pacing as shown by a larger slope and then increased gradually as the paced heart rate increased, as shown by a smaller slope. 14 New data reported here shows that patients with CI have significantly greater prolongation of AV intervals than CC patients. These results are summarized in Table 2.…”
Section: Av Interval Changes In CI and Cc Patients At Restmentioning
confidence: 48%
“…As shown previously, ARV and ALV intervals increased rapidly in all subjects from atrial sense to atrial pacing as shown by a larger slope and then increased gradually as the paced heart rate increased, as shown by a smaller slope. 14 New data reported here shows that patients with CI have significantly greater prolongation of AV intervals than CC patients. These results are summarized in Table 2.…”
Section: Av Interval Changes In CI and Cc Patients At Restmentioning
confidence: 48%